Classification and indexing in the social sciences - Foskett, D. J. (Washington, D.C. : Butterworths, 1963)
The author in this book attempts to address the social scientists themselves in the hope of clarifying a little of the role of information services in social science, as well as describing some recent advances in the design of its equipment.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Classification; Social sciences